2001
DOI: 10.1152/ajplung.2001.280.3.l421
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2regulates wound closure in airway epithelium

Abstract: Repair of the airway epithelium after injury is critical for the maintenance of barrier function and the limitation of airway hyperreactivity. Airway epithelial cells (AECs) metabolize arachidonic acid to biologically active eicosanoids via the enzyme cyclooxygenase (COX). We investigated whether stimulating or inhibiting COX metabolites would affect wound closure in monolayers of cultured AECs. Inhibiting COX with indomethacin resulted in a dose-dependent inhibition of wound closure in human and feline AECs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…Another recent study clearly demonstrated that specific inhibition of COX-2 activity by NS-398 or nonspecific inhibition of COX activity by indomethacin causes a significant delay in wound healing in rat skin (Futagami et al, 2002). In contrast, the addition of PGE 2 -stimulated wound closure in airway epithelium (Savla et al, 2001). Together, these findings suggest that COX-dependent metabolites play a role in stimulating wound healing in various tissues.…”
Section: Effects Of Diclofenac On Tendon Inflammation and Regenerationmentioning
confidence: 98%
“…Another recent study clearly demonstrated that specific inhibition of COX-2 activity by NS-398 or nonspecific inhibition of COX activity by indomethacin causes a significant delay in wound healing in rat skin (Futagami et al, 2002). In contrast, the addition of PGE 2 -stimulated wound closure in airway epithelium (Savla et al, 2001). Together, these findings suggest that COX-dependent metabolites play a role in stimulating wound healing in various tissues.…”
Section: Effects Of Diclofenac On Tendon Inflammation and Regenerationmentioning
confidence: 98%
“…Furthermore, inhibitor studies indicate that LOX metabolites regulate reepithelialization in wounded corneas (11). Another oxidative enzyme of AA, cyclooxygenase (COX-1/2), also may be involved in wound healing because it appears to be associated with directed cell motility and new tissue growth in corneal endothelium, airway epithelium, and skin (15,16,27). How these two eicosanoids coordinately regulate wound closure, however, remains to be elucidated.…”
mentioning
confidence: 99%
“…It is utilised in the treatment of diseases such as osteoarthritis, rheumatic arthritis (Sadowski and Steinmeyer, 2001), gout, cancer and in the prevention of cardiovascular diseases and gynaecologic diseases (Pai et al, 2001) and also used to alleviate the pain after damage or surgery in the tendons and ligaments (Riley et al, 2001). According to some studies (Collier and Ghosh, 1991;Leroux and Saffar, 1993;Guez et al, 2001;Pai et al, 2001;Riley et al, 2001;Forslund et al, 2003;Cohen et al, 2006;Azoubel et al, 2007) indomethacin can interfere in the restoration of the tissue of many organisms, since it inhibits the action of the ciclooxygenase enzyme and consequently the conversion of arachidonic acid into prostaglandin, elements that perform important functions in cell protection, growth, angiogenesis and extracellular matrix production (Savla et al, 2001).…”
Section: Discussionmentioning
confidence: 99%